Effect of packaging techniques and chlorination on the quality and shelf life of country bean (Lablab niger) (Bangladesh Journal of Agricultural Research, 2010)
The experiment was conducted to evaluate the effect of packaging materials on the quality and shelf life of country bean (Lablab niger) using passive modification of modified atmosphere packaging system. The modified atmosphere was created by making perforation in the packets made by polypropylene. Bean pre-treated with chlorine water and then packaging in selected polypropylene resulted substantial reduction in losses caused by weight loss and rotting/shriveling. These treatment combinations also considerably retained vitamin C, β-carotene, moisture content, etc. Under this condition, the retention of quality and shelf life of bean could be extended upto 8 days at ambient condition as compared to non-treated and without packaging. Key Words: Packaging techniques; chlorination; shelf life; country bean.  DOI: 10.3329/bjar.v34i4.5838Bangladesh J. Agril. Res. 34(4) : 623-631, December 2009